Development Banks : Role and Mechanisms to Increase their Efficiency - Gutierrez, Eva; Rudolph, Heinz P.; Homa, Theodore; Blanco Beneit, Enrique (2012)
Past performance of development banks, has generally been considered poor and the value of state ownership questioned. There are few institutions that achieve the optimum balance of effectively addressing a policy objective while being financially sustainable. Following the financial crisis, there is a renewed interest in the role development banks can play in weathering the crisis. The purpose of this paper is to highlight the lessons learned following the financial crisis and to present some of the best practices in development banking so that policy makers can be better informed should they be considering how to build strong state financial institutions to address current and future needs in their respective countries.